2020
DOI: 10.5194/acp-2019-984
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pan-Arctic surface ozone: modelling vs measurements

Abstract: <p><strong>Abstract.</strong> Within the framework of the International Arctic Systems for Observing the Atmosphere (IASOA), we report a modelling-based study on surface ozone across the Arctic. We use surface ozone from six sites: Summit (Greenland), Pallas (Finland), Barrow (USA), Alert (Canada), Tiksi (Russia), and Villum Research Station (VRS) at Station Nord (North Greenland, Danish Realm), and ozonesonde data from three Canadian sites: Resolute, Eureka, and Alert… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 53 publications
(83 reference statements)
0
5
1
Order By: Relevance
“…GEM was averaged to a time resolution of 0.5 h. The new analysis confirmed the previous result, though the data points were more scattered, and thus, the resulting slope had a higher uncertainty, mostly due to smaller difference between the initial GEM concentration and the final concentration. An important point regarding the parameterisation of GEM depletion is that bromine-induced atmospheric mercury depletion events (AMDEs) were often observed under stagnant wind conditions and not only during situations with strong wind that may cause bromine release as proposed earlier (see Yang et al, 2020). Recently, the bromine-induced oxidation of Hg 0 has been proven directly in a study, where Br, BrO, O 3 , GEM and gaseous oxidised mercury (GOM) were measured simultaneously during AMDE and ODE, using a multiphase box model to study the complex set of processes (Wang et al, 2019).…”
Section: Changes In Atmospheric Chemistrymentioning
confidence: 90%
See 1 more Smart Citation
“…GEM was averaged to a time resolution of 0.5 h. The new analysis confirmed the previous result, though the data points were more scattered, and thus, the resulting slope had a higher uncertainty, mostly due to smaller difference between the initial GEM concentration and the final concentration. An important point regarding the parameterisation of GEM depletion is that bromine-induced atmospheric mercury depletion events (AMDEs) were often observed under stagnant wind conditions and not only during situations with strong wind that may cause bromine release as proposed earlier (see Yang et al, 2020). Recently, the bromine-induced oxidation of Hg 0 has been proven directly in a study, where Br, BrO, O 3 , GEM and gaseous oxidised mercury (GOM) were measured simultaneously during AMDE and ODE, using a multiphase box model to study the complex set of processes (Wang et al, 2019).…”
Section: Changes In Atmospheric Chemistrymentioning
confidence: 90%
“…Today, China accounts for about 40 % of the global Hg emissions (Muntean et al, 2014;Streets et al, 2019Streets et al, , 2017Streets et al, , 2018. In North America, Europe and on the North Atlantic, there is a decline in the GEM concentration of between −1.5 % yr −1 and −2.2 % yr −1 (Zhang et al, 2016). In the Arctic, the decline is zero at Svalbard and −0.9 % at Alert (Cole et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…There are also several studies which tried to model tropospheric BrO plumes. Yang et al (2020) used both a chemistry transport and a chemistry climate model to model tropospheric BrO and compared the outputs with satellite columns and ground-based measurements. Fernandez et al (2019) provided 4 years of polar spring comparisons between GOME-2A instrument columns and model runs, for the Arctic and Antarctic, having implemented polar halogen chemistry into the CAM-Chem model.…”
Section: Time Seriesmentioning
confidence: 99%
“…Model studies on polar aerosols also demonstrate an improved agreement compared to sea salt observations for winter and spring when blowing snow sourced sea salt aerosols are included (Rhodes et al, 2017;Huang et al, 2018). Further, this has been recently shown to improve model predictions of BrO and O 3 (Huang et al, 2020;Yang et al, 2020). Finally, observations show that aerosols can sustain bromine activation above the boundary layer (Peterson et al, 2017), but it has not yet been clearly demonstrated from measurements that blowing snow sourced sea salt aerosols trigger bromine explosion events.…”
Section: Accepted Articlementioning
confidence: 91%